Evaluasi Kinerja PT Bank Perkreditan Rakyat Pesisir Akbar Kabupaten Bima, Nusa Tenggara Barat - R Rizki Andhitya Yunanto; Ma'mun Sarma; Darwin Kadarisman (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Coastal communities made up of fishermen, fish farmers, processors and traders of fishery products, businesses and services maritime industry as well as other communities living in coastal areas and small islands. BPR Pesisir Akbar in Bima Nusa Tenggara Barat is one of the six Coastal BPR in Indonesia which has one mission welfare of coastal communities around the operational area. The study aims to (1) Determine the influence of the level of financial and non-financial performance of PT BPR Pesisir Akbar, (2) analyze the factors that affect performance. Performances Evaluation of PT BPR Pesisir Akbar  has done well for non-financial and financial performances.  Non Financial Performances include the number and level of customer satisfaction, while the financial evaluation includes capital, value assets, profit/loss, ROA (Return On Assets), CAR (Credit Adequacy ratio), BOPO (Expenses and Operating Income), NPL (Non Performing Loan), and LDR (Loan to Deposit ratio). Evaluation results show that non-financial public services, credit services, and promotion services jointly or individually significant effect on customer satisfaction, where public service is the strongest factor. Evaluation of financial performance shows PT. PT. BPR Pesisir Akbar relatively well for the development of asset value, earnings, CAR, NPL and ROA, but the increase is relatively small capital and BOPO and LDR have not been good until now.